2006
DOI: 10.1055/s-2006-925405
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Functional FABP2 Promoter Haplotype and Type 2 Diabetes

Abstract: Fatty acid-binding protein 2 (FABP2) is a cytosolic protein expressed exclusively in epithelial cells of the small intestine. Some, albeit not conclusive, evidence indicates that the Thr-allele of FABP2 Ala54Thr polymorphism is associated with type 2 diabetes. More recently, common FABP2 promoter polymorphisms have shown association with postprandial increase of triglycerides, body composition and plasma lipid levels. Therefore, we reasoned that variants in the FABP2 promoter may also predispose to type 2 diab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
26
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 20 publications
4
26
0
Order By: Relevance
“…In this regard, Fabp2 –/– mice represent a model of extreme attenuation of FABP2 gene promoter function. Similar polymorphisms have also been found in other human populations [36,37,38,39]. The FABP2 ‘promoter B’ variant [38] which shares the same deletion found in the Pima Indian FABP2 T54 gene promoter was found to be associated with both the A54 and T54 alleles in a German cohort [37], and individuals from this cohort who are homozygous for both the promoter B and T54 alleles exhibit increased postprandial lipemia and lower insulin sensitivity [37].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In this regard, Fabp2 –/– mice represent a model of extreme attenuation of FABP2 gene promoter function. Similar polymorphisms have also been found in other human populations [36,37,38,39]. The FABP2 ‘promoter B’ variant [38] which shares the same deletion found in the Pima Indian FABP2 T54 gene promoter was found to be associated with both the A54 and T54 alleles in a German cohort [37], and individuals from this cohort who are homozygous for both the promoter B and T54 alleles exhibit increased postprandial lipemia and lower insulin sensitivity [37].…”
Section: Discussionsupporting
confidence: 87%
“…The FABP2 ‘promoter B’ variant [38] which shares the same deletion found in the Pima Indian FABP2 T54 gene promoter was found to be associated with both the A54 and T54 alleles in a German cohort [37], and individuals from this cohort who are homozygous for both the promoter B and T54 alleles exhibit increased postprandial lipemia and lower insulin sensitivity [37]. However, the interplay between FABP2 promoter B and A54 and T54 alleles requires further clarification since the FABP2 promoter B was found to be associated with reduced risk of type 2 diabetes in male subjects of another German cohort [38]. …”
Section: Discussionmentioning
confidence: 99%
“…All amplifications were performed for 30 cycles at 951C for 45 seconds, a touchdown from 581C to 541C for 30 seconds, and 721C for 1 minute in a buffer containing 2 mM MgSO 4 , 10 mM dNTP, and 0.5 U Pfu polymerase. Cloning procedures were performed using Gateway Technology (Invitrogen, Karlsruhe, Germany), described previously [Li et al, 2006]. attR-sites were inserted into an EcoRV (Promega, Mannheim, Germany) blunt-end site of the reporter plasmid pGL4.10[luc2] encoding Firefly luciferase.…”
Section: Mttp (Geneid: 4547) Promoter-reporter Constructsmentioning
confidence: 99%
“…More recently, FABP2 promoter haplotypes were associated with postprandial triglyceride levels [Geschonke et al, 2002], body mass index (BMI) [Damcott et al, 2003], and type 2 diabetes . The FABP2 coding and promoter polymorphisms are in strong or complete linkage disequilibrium (D 0 0.6-1.0) [Damcott et al, 2003;Formanack and Baier, 2004;Li et al, 2006]. In accordance with the association studies, male FABP2 knockout mice showed key symptoms of the metabolic syndrome such as increased plasma levels of insulin and triglyceride, increased body weight, and changes in liver histology, possibly resulting from impaired lipid metabolism [Agellon et al, 2006;Vassileva et al, 2000].…”
Section: Introductionmentioning
confidence: 99%